Analisis Fasilitas Penunjang Pembelajaran Di Sekolah Dalam Menghadapi Tantangan Era Digital - Ainan Safiinatunnajah; Faiza Azka Salsabila; Khaula Maritza Sulaeman; Rafa Anindita Az Zahra (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Learning in the digital era needs to be supported by various supporting facilities. Variations in student needs and school capabilities affect the differences in the procurement of relevant supporting facilities. This study aims to analyze learning support facilities in public and private schools in West Java. Data was collected by interviewing teachers from each school. The results of this study show that both schools have different facilities and facilities to support the digita era. SDIT Titian Ilmu has more equitable and complete digital facilities compared to SDN 087 Rancabolang. This shows that schools in Indonesia are uneven in terms of digital facilities, especially in public schools. Nevertheless, both schools have realized the importance of keeping up with the times to support the learning process. These schools have used digital learning to support the learning process. However, SDN 087 Rancabolang still has limited digital facilities due to the uneven distribution of facilities within the school which only provides one infocus that is used alternately and the internet (WIFI), while SDIT Titian Ilmu, the facilities and facilities are evenly distributed, namely infocus in each class and a computer lab. However, teachers at SDN 097 Rancabolang do not just let this digital-based learning continue, but they try to familiarize themselves with the use of this technology.